Sistem Pakar Berbasis Dekstop Untuk Mendeteksi Penyakit Pada Ikan Mas Menggunakan Metode Certainty Factor (Kasus Di Pusat Pelatihan Mandiri Kelautan Dan Perikanan SINI SUKA Biru-biru Sumatera Utara) - Siti Agus Kartini; Puji Chairu Sabila; Richard Parlindungan Simanjuntak (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Goldfish (Cyprinus carpio) is a freshwater fish that has important economic value and has spread widely in Indonesia. Goldfish are one of the most recognizable fish species in the world. It is found worldwide as a pet. Where the level of consumption of this fish is very high in all circles of society, because in general all humans eat fish every day to add nutrition, but problems that arise if you are unable to master the technique of controlling it in terms of disease cause enormous losses for fish farmers. Disease is one of the causes of many fish deaths. One of the fish is infected with the disease, then the disease will spread throughout the pond. This will result in huge losses. This study aims to detect fish diseases more precisely and quickly with the help of a computer. The method used is the Certainty Factor by taking data from the Maritime and Fisheries Independent Training Center SINI SUKA Biru-biru, North Sumatra. By using data on symptoms and diseases in goldfish and then assigning a weight value to each symptom and calculating according to the steps of the Certainty Factor method with an accuracy close to 100%, this method can be applied to detect goldfish disease so that this research is very very helpful in identifying goldfish disease.